Efficacy of nasopancreatic stenting prior to laparoscopic enucleation of pancreatic neuroendocrine tumor. Issue 2 (22nd April 2013) - Misawa, Takeyuki; Imazu, Hiroo; Fujiwara, Yuki; Kitamura, Hiroaki; Tsutsui, Nobuhiro; Ito, Ryusuke; Shiba, Hiroaki; Futagawa, Yasuro; Wakiyama, Shigeki; Ishida, Yuichi; Yanaga, Katsuhiko
Abstract We report a patient who underwent laparoscopic enucleation for a nonfunctioning pancreatic neuroendocrine tumor. The patient was a 55‐year‐old man who had a 12‐ × 11‐mm tumor close to the main pancreatic duct (MPD) in the pancreatic body. To avoid and detect injury to the main pancreatic duct during operation, a nasopancreatic drainage stent (NPDS) was endoscopically placed prior to the operation. According to the NPDS, the relation between the tumor and MPD was easily identified by laparoscopic ultrasonography during enucleation, thus enabling the resecting line to be determined. Moreover, after enucleation, pancreatography through the NPDS was able to clarify the absence of injury to the MPD. The NPDS was removed postoperatively, and the patient was discharged uneventfully on postoperative day 8. Preoperative placement of the NPDS seems to be a useful option for performing safe laparoscopic enucleation of pancreatic neuroendocrine tumor, especially when the lesion is located close to the MPD.